The need for action by evaluators and decision makers in Europe to ensure safe use of medical software - Mattias Kyhlstedt (Frontiers in Medical Technology, 2022)
Digital Health Solutions (DHS) approved under the Medical Device Directive (MDD) in the European Union may be used until May 27, 2025. The regulation provides appropriate requirements for the products but lack the evaluation by an external independent organization. For many DHS, the company can make a self-certification that the requirements have been fulfilled. As demonstrated in the evaluation of smartphone-based apps for skin cancer risk assessment such products may expose the public to undue risks. The new Medical Device Regulation provides adequate control of DHS through evaluation of independent organization prior to allowing the product on the market. HTA-evaluators and those who make decisions regarding the use of DHS need to understand the associated risks with the use of products approved according to the MDD and ensure appropriate risk mitigations to ensure that the public is not exposed to undue risk. This perspective aims to inform decisionmakers about the risks associated with the delayed requirement to transition to the new MDR regulation. There is a gap in the current guidance regarding the evolving use of machine learning and artificial intelligence. With the evolving use of DHS, it is important that industry, regulators and HTA evaluators work jointly to establish the safe and effective use of DHS.